A Comparative Study on the Self Diffusion of N-Octadecane with Crystal and Amorphous Structure by Molecular Dynamics Simulation - 饶中浩 刘新健 张瑞凯 李响 魏昌兴 王浩东 李意民 (Chinese physics letters, 2014)
The straight chain n-Mkanes and their mixture, which can be used as phase change materials （PCM） for ther- mal energy storage, have attracted much attention in recent years. We employ the molecular dynamics （MD） simulation to investigate their thermophysical properties, including self diffusion and melting of n-octadecane with crystal and amorphous structures. Our results show that, although the initial and melted structures of n-octadecane with crystal and amorphous are different, the melting behaviors of n-octadeeane judged by the self diffusion behavior are consistent. The MD simulation indicates that both the crystal and amorphous structures are effective for the property investigation of n-octadecane and the simulated conclusion can be used as reference for modeling the alkanes-based PCM system.